Cryptocurrency market analysis from the open innovation perspective - Alexey Mikhaylov (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The paper focuses on the analysis of the cryptocurrency open innovation market to predict sustainable growth in the future. The nature of cryptocurrencies 'development leads to the rapid increase in their popularity and spread of trading at this new market. The high volatility of these assets is encouraging to understand and predict their price in ever changing market environment. The paper proposed the pool complexity approach to choose optimal technology using social activity in the internet, trading parameters, technical indicators and other cryptocurrency data. According to the results of the analysis, the most effective and promising cryptocurrency is EOS cryptocurrency, which has the lowest complexity and commission level among the analyzed digital currencies and allows you to implement third-party applications in the system.
Keywords: 650; Bitcoin; cryptocurrency; data selection; EOS; ethereum